Bioconversion of potato waste by rumen fluid from slaughterhouses to produce a potential feed additive rich in volatile fatty acids for farm animals. (20th January 2021) - Pourbayramian, R.; Abdi-Benemar, H.; Seifdavati, J.; Greiner, R.; Elghandour, M.M.M.Y.; Salem, A.Z.M.
Abstract: Potato waste, usually derived from storage and processing of potatoes, is an agricultural byproduct already used as a feed for ruminants. Its fermentation using rumen fluid, another waste product obtainable from slaughterhouses, is expected to valorize both products. Bioconversion of potato waste using rumen fluid was followed by measuring volatile fatty acids (VFAs), pH, and the extent of digestion of the potato waste as well as the nutrient composition of the solid residues after fermentation. Different ratios (1:2, 2:2, 3:2 and 4:2 w dry matter/v) of potato waste to rumen fluid were fermented in a Daisy II incubator for 12 or 24 h at 39 °C. Depending on the fermentation time and the dry mass of potato waste used for fermentation, a digestion rate between 31 and 78.8% of the potato waste (solid phase of the fermentation mixture) was obtained. Fermentation resulted also in an up to 2.5-fold increase in the concentration of VFAs in the liquid phase of the fermentation mixture. During fermentation, the pH value of the fermentation mixture dropped from 6.95 to about 4.0 (P < 0.05). The highest digestion rate and the highest VFA production were obtained with 100 g potato waste and a 24 h fermentation time. Furthermore, the residual solid residues after fermentation had higher protein and fat contents compared to the potato waste used for fermentation (P < 0.05). Based on the results obtained, potential applications of both potato wastes and rumen fluids have been identified. The used method for bioconversion is suggested for scale-up purposes. Highlights: The two waste products, potato waste and rumen fluid, were successfully valorized. Digestion rates up to 78.9% for potato waste were obtained. A 2.5-fold increase in the concentration of total volatile fatty acids was achieved. The solid parts of the fermentation mixture had a higher protein content. Potential applications of both potato wastes and rumen fluids have been identified.